PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN ISLAMIC FAITH EDUCATION SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA ISLAM AL ABIDIN SURAKARTA TAHUN AJARAN 2023/2024 - Muhammad Khalifah Al Madani; Imam Suhadi; Muh. Hasbi Khilal Zuhri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The Merdeka Curriculum provides teachers with the flexibility to create high-quality learning tailored to students' needs and learning environments. Its introduction aims to enable students to freely choose the best path for developing their potential through learning. This study focuses on understanding the role of Islamic Religious Education (PAI) teachers in implementing the Merdeka Curriculum for the Islamic Faith Education subject at Islamic Junior High School Al Abidin Surakarta. The research findings indicate that Islamic Religius Education Teachers at Islamic Junior High School Al Abidin Surakarta play a crucial role in implementing the Merdeka Curriculum for Islamic Faith Education. During the implementation process, teachers motivate students, adapt teaching materials to their needs, and provide classroom guidance. Teachers not only impart religious knowledge but also teach students to apply Islamic values in their daily lives.